A novel PrECOG (PrE0901) dose-escalation trial using eltrombopag: enhanced platelet recovery during consolidation therapy in acute myeloid leukemia. Issue 9 (28th July 2020) - Strickland, Stephen A.; Wang, Xin Victoria; Cerny, Jan; Rowe, Jacob M.; Rybka, Witold; Tallman, Martin S.; Litzow, Mark; Lazarus, Hillard M.
Abstract: High-dose cytarabine (HiDAC) consolidation for acute myeloid leukemia (AML) induces transient profound myelosuppression and potential morbidity/mortality. PrE0901 was a phase I multi-center trial evaluating the safety/toxicity of eltrombopag in AML patients receiving HiDAC consolidation. We used a standard 3 + 3 design employing a unique dose-escalation/de-escalation strategy. One hundred four patients were screened, 54 declined participation, 35 were deemed medically ineligible, and 14 were treated on study. Three patients were treated in cohorts 1–4 and two were treated in cohort 5. Eltrombopag + HiDAC was well-tolerated and no dose-limiting toxicities were observed. Median time to platelet recovery of all patients treated was 22.5 (range 16–43) days. Observationally, eltrombopag 150 mg once daily starting on day 3 of consolidation demonstrated the fastest and most consistent platelet recovery (median 19 days). Further investigation is needed to define the optimal role, dose, and schedule of eltrombopag in the treatment of chemotherapy associated myelosuppression.